Enhancement of recycled aggregate concrete properties through the incorporation of nanosilica and natural fibers - Sattawat Haruehansapong; Prachoom Khamput; Pruchaya Yoddumrong; Wunchock Kroehong; Vichayaphong Thuadao; Akkadath Abdulmatin; Wachirakorn Senawang; Tawich Pulngern (Heliyon)
This study introduces an innovative approach to enhancing recycled aggregate concrete (RAC) by incorporating nanosilica (NS) and natural fibers (NF), specifically sisal fiber (SF) and palm fiber (PF). This novel combination aims to overcome the inherent limitations of RAC, such as reduced strength and durability, while promoting sustainability in construction. The research focuses on evaluating the mechanical properties of RAC, including compressive and flexural strengths, through the integration of NS and NF. Our findings reveal that NS significantly improves the microstructure of RAC by enhancing the interface transition zone (ITZ) and filling nanovoids, resulting in a denser and more durable concrete matrix. Specifically, the addition of 3 % NS increased the compressive strength of RAC by up to 22.5 % and the flexural strength by up to 25.6 % at a 100 % replacement ratio of recycled aggregate. The addition of NF, treated to withstand the alkaline environment of concrete, further strengthens the RAC by providing a bridging effect that enhances flexural strength by up to 46.7 %. This work not only advances the performance of recycled concrete but also aligns with the broader goal of environmental sustainability by utilizing waste materials and reducing the carbon footprint of concrete production. The findings have the potential to influence future construction practices, encouraging the adoption of more durable and eco-friendly building materials.